PERFORMA REPRODUKSI IKAN BANDENG (CHANOS CHANOS FORSSKAL) SKALA HATCHERY - NI LUH MUTIARA PEBRIANTI; RANGGA IDRIS AFFANDI (Universitas Mahasaraswati K. Mataram, 2024)
Milkfish (Chanos chanos Forsskal) is a food fish that is spread across several regions in Indonesia. Milkfish is quite high in protein, making the digestive process easier for the body when consumed by people of all ages. This causes an increase in demand for this fish on the market, both in local and international markets. This increase in production causes demand for seeds to also increase. However, this request often cannot be fulfilled. This is because the availability of seeds is limited. This research aims to determine the reproductive performance of hatchery scale milkfish. This research activity was carried out in March-April 2023 at the Center for Brackish Water Aquaculture Fisheries (BBPBAP) Jepara, Central Java. The data collection techniques used in this research were descriptive methods and field observations. The results obtained were milkfish hatchery activities including broodstock rearing, handling eggs, checking water quality, enriching broodstock feed, feeding broodstock, as well as larval rearing activities until harvest. Milkfish have euryhaline properties, can spawn more than once a year with an average number of eggs >200,000 eggs for each spawning